Androgen receptor expression in the rat prostate is down-regulated by dietary phytoestrogens - Handa Robert J; Adlercreutz Herman; Lund Trent D; Munson Daniel J; Lephart Edwin D (BMC, 2004)
Abstract Background It is well established that the growth of the prostate gland is a hormone-dependent phenomenon involving both androgenic and estrogenic control. Proliferation of prostate cells is, at least in part, under control of estrogen receptor beta (ER-beta). Phytoestrogens bind ER-beta with high affinity and therefore may have antiproliferative effects in the prostate. Methods The prostates of male Long-Evans rats fed a diet high in phytoestrogens (Phyto-600) or very low levels of phytoestrogens (Phyto-free) were analyzed to determine the impact of dietary phytoestrogens on prostate weight and androgen receptor (AR) expression in the prostate. Results Dietary phytoestrogens significantly decreased post-pubertal prostate weight gain in Phyto-600 vs Phyto-free fed males. Additionally, dietary phytoestrogens (Phyto-600) decreased AR expression in the prostate as determined by in situ hybridization. Conclusions Soy phytoestrogens, present in diet, alter prostate growth presumably by binding ER-beta and subsequently reducing AR expression within the prostate.